Identification of an Invertase With High Specific Activity for Raffinose Hydrolysis and Its Application in Soymilk Treatment - Liu, Juanjuan; Cheng, Jing; Huang, Min; Shen, Chen; Xu, Ke; Xiao, Yazhong; Pan, Wenjuan; Fang, Zemin (Frontiers in Microbiology, 2021)
Raffinose is a candidate prebiotic of humans but leads to flatulence in the gut. Unlike using α-galactosidases to hydrolyze raffinose into sucrose and galactose, hydrolyzing raffinose into melibiose using invertases under mild conditions would improve the nutritional value of soybean products. However, little attention has been paid to this strategy due to the lack of suitable invertase. In the present study, a novel invertase, named InvDz13, was screened, purified, and characterized from Microbacterium trichothecenolyticum. InvDz13 represented one of the invertases with the highest specific activity towards raffinose, which was 229 U/mg at pH 6.5 and 35 oC. It retained more than 80% of the highest activity at pH 5.5-7.5 and 25-40 oC and resistant to or was stimulated by most cations in soymilk. After treating the soymilk with InvDz13 at mild conditions, the melibiose concentration doubled due to the hydrolyzation of raffinose by InvDz13. Furthermore, the prebiotic property of the InvDz13-treated soymilk was investigated via in vitro fermentation by human gut microbiota. The results showed that it increased the proportion of some beneficial bacteria, such as Bifidobacterium and Lactobacillus, but dramatically decreased the population of gas-producing bacteria, including Escherichia and Collinsella. Thus, InvDz13 has remarkable application potential in melibiose preparation during soymilk production.